Edukasi K3L kepada Tenaga Kerja Proyek Peningkatan Jalan Pulokulon-Tuko R.55 Kecamatan Pulokulon Kabupaten Grobogan - Etika Herdiarti; Fitria Maya Lestari; Risdiana Cholifatul Afifah (Faculty of Engineering, Universitas Semarang, 2024)
Occupational safety, health, and environment (OSH) is inseparable from the labor and human resources system. Not only are safety, health and the work environment very important for employees, but safety, health, and the work environment also determine workplace productivity. According to Law Number 13 of 2003 concerning Employment, what is meant by employment for workers is the obligation to provide protection, including the welfare of body and soul, safety, and health of workers. Companies take various steps to protect their employees from the dangers of work accidents. Personal Protective Equipment (PPE) is an effort to protect part or all of the body from the potential hazards of work accidents and occupational diseases. This activity aims to foster a sense of responsibility among workers regarding the importance of implementing OSH so that they can minimize the number of work accidents. The method used in socialization is lectures. The results obtained are an increase in workers' understanding and discipline regarding the importance of OSH in the field.